â€œAn Analysis Of The Effect Of The Number Of Population, Economic Growth, Provincial Minimum Wage, and Inflation On Rate Of Unemployment In Indonesia 2010-2014â€ - B01112039, Kinanti Nawang Wulan Nawang Wulan (Jurnal Pembangunan dan Pemerataan, 2016)
Growth, Provincial Minimum Wage, and Inflation On Rate Of Unemployment In Indonesia 2010-2014â€AbstractUnemployment is a condition where a person does not have job or is looking for a job but has not got it. Unemployment is a problem of every country in the world, and it can generate losses both for the unemployed themselves, society, and the State. The purpose of this research is to find out the effect of the number of population, economic growth, provincial minimum wage, and inflation on the rate of unemployment in Indonesia from 2010 to 2014.This is both a quantitative and an explanatory research. The data used in this research werw pooled data i.e. a combination of time series and cross section data. This research used secondary data obtained from the book Statistik Indonesia 2011 â€“ 2015 published by the Central Statistics Agency (BPS) Indonesia. The data were analyzed using multiple a linear regression analysis. The hypohesis was tested using partial test (t-test), simultanous test (f-test), determinant coefficient test (R2).The findings showed that number of population had a significant negative correlation to unemployment in Indonesia; economic growth had a insignificant positive correlation to unemployment in Indonesia; the provincial minimum wage had a significant negative correlation to unemployment in Indonesia; and inflation had a significant positive correlation to unemployment in Indonesia. Meanwhile, simultaneously number of population, economic growth, provincial minimum wage, and inlfation had a significant effect on unemployment in Indonesia from 2010 to 2014.Keywords: unemployment, number of population, economic growth, provincial minimum wage, inflation